PENGARUH KEADILAN DISTRIBUTIF, KEPATUHAN PENGENDALIAN INTERNAL, DAN LOVE OF MONEY TERHADAP KECENDERUNGAN KECURANGAN PENGGUNAAN DANA DESA - Ni Luh Putu Agustiari Sisca Dewi; Ni Komang Sumadi (Hita Akuntansi dan Keuangan, 2020)
Fraud isl anl intentionall act by one orl more individuals inl management orl those responsible forl governancel, employeesl, andl third parties thatl involves thel use ofl guile to gainl anl unfair advantage orl breakl thel lawl. Generally thel tendency ofl fraud occurs because ofl pressure to commit fraud orl encouragement to take advantage ofl opportunities thatl existl. Thisl research aims to examine andl re- analyze thel influence ofl thel variables ofl distributivel justicel, compliance with internall control andl lovel ofl moneyl onl thel tendency ofl fraudulent use ofl village fundsl. Thel populationl inl thisl study were all village officials andl all BPD members inl thel Kerambitanl District ofl Tabananl Regencyl, while thel sample wasl 135 peoplel. Thel method ofl determiningl thel sample inl thisl study uses a purposivel samplingl techniquel. Datal collectionl wasl carried outl through a questionnaire thatl wasl distributed directlyl. Datal analysisl method used isl multiple linearl regressionl analysisl. Thel results ofl thisl study indicate thatl thel variables ofl distributivel justice andl lovel ofl moneyl havel positivel andl significant effects onl thel tendency ofl fraudl, while internall control compliance hasl a negativel andl significant effect onl thel tendency ofl fraudl.